Implementation of Independent Learning in Independent Campus at the Islamic University of Malang : Education Personnel Perspective - Dwi Fita Heriyawati; Ifit Novita Sari; Noni Mia Rahmawati; Sonny Elfiyanto (STAI Miftahul Ula Nganjuk, 2022)
The application of an independent campus is not only limited to learning carried out on campus, especially for lecturers as the main key, but also for education staff. Therefore, as educators, interpersonal skills are needed to work together and the ability to communicate, lead, motivate students, and even interact with their own superiors and other people outside their work area. This study aims to find out to what extent the readiness of education personnel at the Islamic University of Malang in implementing MBKM. The research method used is a survey. Respondents are all education staff in the Islamic University of Malang, both those in the Undergraduate Study Program, Faculties other than the Faculty of Health, Units, Institutions, and Bureaus with a total of 328 respondents. The instrument used for the survey is an instrument prepared by the Ministry of Education and Technology through the link: http://survey.spadadikti.id/61b8c03c205fb36c71698a3a. The results showed that most of the respondents stated that the MBKM program can improve student learning processes, increase students' hard-skills and soft-skills, be involved in the socialization process, can increase the capacity and ability of educators, and be involved in the MBKM program at the Islamic University of Malang.